PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN KELUARGA YANG TERDAFTAR DI BEI PERIODE TAHUN 2013-2017 - Intan Ariningtyas Junaidi; Nurfauziah Nurfauziah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2019)
The purpose of this study was to determine the effect of the application of good corporate governance to the value of the company in family businesses. In this study the sample used was 50 family companies listed on the Indonesia Stock Exchange in 2013-2017. This sample uses a purposive sampling method based on predetermined criteria. The corporate governance mechanism used is an independent board of commissioners and an audit committee. The company value is calculated using the book value (PBV). In testing hypotheses, the method used is multiple regression analysis. The results of this study indicate that if the independent board of commissioners has no influence on the value of the company measured using the book value of prices and the audit committee has a positive influence on the value of the company measured using the book value of prices.